The Moderating Effect of Institutional Ownership on Intellectual Capital and Financial Performance of Listed Conglomerates - Isah Umar Kibiya; Bilyaminu Shittu Aminu; Khadija Salihu Abubakar (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose - The study aims to examine the moderating effect of institution on the relationship between intellectual capital on the financial performance of conglomerates in Nigeria Design/Methodology - correlational research design which is based on historical data extracted from annual report and accounts of the sample firm on NSE. Firms were chosen based on censor sampling method. Eleven years of financial data were used. Multiple regression analysis was employed to analyze the data extracted. Findings - The results from pooled ordinary least square regression (OLS) and Fixed effect revealed that intellectual capital indexed by a value-added intellectual coefficient (VAIC) has a positive and significant impact on financial performance indexed by return on asset (ROA) of listed conglomerate firms in Nigeria. Furthermore, the interaction effect of institutional ownership was found to be positive and significant Practical Implications - The study recommends that institutional shareholders should invest more in shares of listed conglomerate firms in Nigeria and that management should recognize the effort and understand the importance of intellectual capital toward improving firm performance.